“In Vitro” Multiplication and Conservation of “Euphorbia Canariensis” L. - PETRUȘ-VANCEA, Adriana; FORDON, Andrei (Studia Universitatis Babeș-Bolyai Biologia, 2016)
The effect of deuterium depleted water (DDW) (25 ppm D) was studied on the second culture of Euphorbia canariensis L., to transfer ex vitro. At 18 months of in vitro culture, on medium which the distilled water (155 ppm D) was replaced with deuterium depleted water (25 ppm D) are found to the root system, plants are capable to transfer into to the soil, compared to control lot, rootedness, with acclimatization unfit plants. The chlorophyll and carotenoids pigments were increased in presence of DDW. At the end of the acclimatization, ex vitro survival rate was raised from 92% to plantlets provided from medium prepared with DDW.